Pengaruh Price Discount Terhadap Keputusan Pembelian Pada Store Azwa Perfume - Rahmad Irfando; Rosmayani Rosmayani (SYNERGY: Jurnal Bisnis dan Manajemen, 2024)
This research was conducted using two variables where variable X is Price Discount and variable Y is Purchase Decision. The aim of using these two variables is to see the influence of the price discount variable on the purchasing decision variable at the Azwa Perfume store Jl. Teuku Umar. In this research, researchers used a census method on Azwa Perfume and all consumers who shopped at Azwa Perfume were used as samples in this research. The data obtained was through observation, questionnaires and interviews which were then analyzed using SPSS Version 22, with the results of testing the hypothesis, which showed that the price discount variable had a significant effect on purchasing decisions. The determination efficiency value was influenced by 0.432 or 43.2%. It can be concluded The influence of price discounts on purchasing decisions at the Azwa Perfume Jl store. Teuku Umar amounted to 0.432 or 43.2%, and the remaining 56.8% was influenced by other factors not examined in this study.Â Â